Dielectric waveguides at submillimeter wavelengths - Weinzierl, Jochen; Fluhrer, C; Brand, Hans (IEEE Sixth International Conference on Terahertz Electronics, 1998)
A flexible waveguide system has been simulated using the field calculation program MAFIA, for the first time realised for frequencies up to 150 GHz and operated in two applications. The flexible waveguide system consists of a rectangular, dielectric fibre made of polyethylene combined with optimised tapers and waveguide adapters, which makes the flexible waveguide easy to use in combination with conventional waveguides. A minimum attenuation of 4 dB/m at 140 GHz; has been obtained with the dielectric waveguides, which is about 6 dB less than the measured attenuation of D-band waveguides operated at the same frequency. Additionally the phase shift of the flexible waveguides for different bending radii as well as the influence of different tapered fibre terminations was measured and is reporte
lhft_intern.bib::weinzierl98